Mitochondrial Complex I, a Possible Sensible Site of cAMP Pathway in Aging - Anna Signorile; Domenico De Rasmo (MDPI AG, 2023)
In mammals during aging, reactive oxygen species (ROS), produced by the mitochondrial respiratory chain, cause oxidative damage of macromolecules leading to respiratory chain dysfunction, which in turn increases ROS mitochondrial production. Many efforts have been made to understand the role of oxidative stress in aging and age-related diseases. The complex I of the mitochondrial respiratory chain is the major source of ROS production and its dysfunctions have been associated with several forms of neurodegeneration, other common human diseases and aging. Complex I-ROS production and complex I content have been proposed as the major determinants for longevity. The cAMP signal has a role in the regulation of complex I activity and the decrease of ROS production. In the last years, an increasing number of studies have attempted to activate cAMP signaling to treat age-related diseases associated with mitochondrial dysfunctions and ROS production. This idea comes from a long-line of studies showing a main role of cAMP signal in the memory consolidation mechanism and in the regulation of mitochondrial functions. Here, we discuss several evidences on the possible connection between complex I and cAMP pathway in the aging process.